Kesulitan Belajar Matematika Materi Penjumlahan dan Pengurangan pada Siswa Kelas III di MI Ma’arif Wotbuwono - Asih, Prasukadana Welas; Subarkah, Imam (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The aims of this research are to find out the types of mathematics learning difficulties experienced by students class III B students at MI Ma’arif Wotbuwono. This research is descriptive research with a qualitative approach. The subjects of this research were class III B teachers and class III B students at MI Ma’arif Wotbuwono with a total of 25 students. The method used in this research is qualitative method. The data collected is in the form of learning implementation data using observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and verification/drawing conclusions. The results of the research conducted show that students have difficulty understanding the concept of addition and subtraction, have difficulty understanding symbols, have difficulty solving word problems, have difficulty recognizing place value, students often make mistakes in writing numbers, and students often make mistakes in calculations because they are not careful.